El uso de la potestad reglamentaria para el desarrollo de consideraciones y la implementación de órdenes de la Corte Constitucional : el caso de las sentencias C-355 de 2006, T-063 de 2015 y T-478 de 2015 (2017)
The Constitutional Court has arranged the enforcement of public policies to the sexual and reproductives rights of women and the LGBTQ rights through orders addressed to the National Government. Thereby, the main difficulty that has arised for the Government has been the related with the selection and use of administrative acts to enable the launching of the established in the Sentences C-355 of 2006, that decriminalized abortion in three exceptional cases; T-478 of 2015, better known as Sergio Urrego case; and T-063 of 2015, that acknowledged the change of sex in identity documents. This, because of that acts have been sued by those who consider that the National Government is not competent to regulate sentences and, instead, is the Congress of the Republic who has to legislate about the issues of that sentences. At the end, those administratives acts sued were declared nulls. This study reveals the judgements of the Council of State...